The Role of Work Effectiveness, Efficiency, and Timeliness on Administrative Services in Gresik - Anis, Mohammad; Burhan, Rachmad Ilham, Umar (YUME : Journal of Management, 2025)
Public administrative services in Indonesia continue to face concerns over delays, repeated service errors, and low satisfaction among residents accessing administrative services. These challenges reflect underlying issues in employee performance and internal work processes. This study investigates the effects of work effectiveness, efficiency, and timeliness on employee performance within the Integrated Administrative Services Unit of the Gresik Sub-District Office. Using a quantitative method with 80 respondents and structured questionnaires, the analysis was conducted through multiple linear regression. Results show that all three variables significantly and positively influence performance, with effectiveness as the most dominant factor. The model accounts for 96% of the variation in employee performance. These findings suggest that performance improvements can be achieved through better work structuring and time management, without the need for complex or costly interventions. The study offers practical insights for local governments seeking to improve public service delivery through simple, targeted internal reforms.Keywords: employee performance, public administration, effectiveness, efficiency, timeliness, administrative services.